Análisis de consorcios bacterianos y grupos funcionales asociados a la rizosfera de la papa (Solanum tuberosum), Var. Súper chola en el piso altitudinal de 3400 msnm. Cotopaxi. 2021 - Cruz Almagro, Francisco Javier (2021)
The present research was carried out in the rhizosphere of the potato, a super chola variety in the altitude floor of 3400 meters above sea level in the community of Cuturuví Chico in the province of Cotopaxi, aimed at identifying bacterial consortia and determining the functional groups associated with the rhizosphere of the potato cultivation. Bacterial identification was carried out through the method of sequencing in nanopores with the MinION device, with amplification of the 16s genes of the sample and preparation of DNA libraries, for sequencing using the barcode kit for subsequent analysis of the resulting readings. in the 16S online bioinformatics flow at EPI2ME. For the analysis of the different functional groups, the methodology of (Bernal, Gustavo, 2005) was taken as a methodological reference, which was used for the determination of nitrogen-fixing bacteria, nitrogen-solubilizing bacteria, fungi, actinomycete, cellulolytic bacteria, pseudomonas. Of the aforementioned functional groups, five repetitions were carried out in soil and root plus a blind control where we obtained the number of colonies * gr-1 and the (Colony-forming units) CFU * gr -1 of each one. Additionally, to know the state of composition of the soil, a physical-chemical analysis was carried out and sent to the INIAP laboratory. From the data obtained in the research, it can be said that Enterobacteriaceae was identified as the dominant families in the soil sample with 34,238 accumulated readings, characterized by being phosphorus solubilizers and nitrogen fixers Followed by Xanthomonadaceae with 2,009 accumulated readings, which are characterized for possessing cellulolytic and nitrogen fixing bacteria. The most dominant genus is Raoultella with 1,949 cumulative readings, which are pathogenic disease-causing bacteria. Followed by Arenimonas with 1,002 accumulated readings, characterized by having phosphorus solubilizing bacteria. the most dominant species is Raoultella ornithinolytica with 1,097 accumulated readings, a species that is characterized by causing pathologies in cultivation. Followed by Arenimonas daechungensis with 949 accumulated readings, this family is characterized by having phosphorus solubilizing bacteria, this could influence the high nitrogen and phosphorus content obtained in the soil analysis with 43 ppm of N and 79 ppm of phosphorus (P) respectively The functional group with the highest number of colonies in this type of soil and altitudinal floor described above were Pseudomonas, where we found 3.56 * 107 Colonies * gr-1 in the soil sample and 3.41 * 107 Colonies * gr-1 in the Root sample which allows us to determine that there is a higher quantity of Pseudomonas in relation to the rest of the functional groups under study. In Colony Forming Units per gram of soil (CFU * gr-1), we find 3.04 * 107 CFU * gr-1 and 2.41 * 1012 in the soil sample of and 2.96 * 107 CFU * gr-1 in the root sample, which allows us to determine that there is a greater quantity of microorganisms associated with the potato rhizosphere in the soil sample.